Effects of Montmorillonite (MMT) Inorganic Fillers on Polyvinylidene (PVDF) Mixed Matrix Membrane - Oh , P.C. (2014)
Asymmetric nanoclay-polyvinylidene (PVDF) mixed matrix membranes (MMMs) were prepared by the reaction of various amount of montmorillonite (MMT) nanoclay mineral with PVDF. The MMMs were fabricated via dry-wet phase inversion method with N,N-dimethyl-acetamide (DMAc) as the solvent and ethanol as the coagulant. The fabricated MMMs were characterized by means of fourier-transform infrared (FTIR) and scanning electron microscopy (SEM). The separation performances of the prepared membranes were evaluated by pure gases (CO2 and CH4). From the FTIR spectrum, MMMs exhibited new peaks compared to pristine PVDF membrane, indicating assimilation of MMT into the PVDF membrane. The morphology of the membranes depends on the clay mineral loading as confirmed by SEM. PVDF/3wt% MMT MMM showed the highest CO2 permeance and CO2/CH4 selectivity relative to neat PVDF membrane.